Peningkatan Motivasi dan Prestasi Belajar IPA Materi Gejala Alam melalui Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) Siswa Kelas VIIG SMP 3 Jekulo Kabupaten Kudus Semester 2 Tahun 2012/2013 - Purwaningsih, Sri; Purniawati, Ida (widiyanto, 2016)
The research objective of this class action is to determine whether the model type STAD cooperative learning can increase the motivation to learn science for students of classes VII G SMP 3 Jekulo district on the materials of symptoms nutare and can determine the increase learning achievement in science for students of classes VII G SMP 3 Jekulo districts the material of symptom nature. This study was conducted over seven months starting from the beginning of November 2012 until May 2013. The results of this study states through cooperative learning STAD (Student Team Achievement Division) can increase the motivation to learn science Symptom nature from the initial condition low learning motivation to conditions high-end motivation to learn science. From the results of the study also mentions through cooperative learning STAD (Student Team Achievement Division) can improve learning achievement Symptom nature on the material of the initial conditions of learning achievement averages 47.5  to the final conditions mean 76.32. It can be concluded both theoretically and empirically that cooperative learning STAD (Student Team Achievement division) can improve learning achievement.Tujuan penelitian tindakan kelas ini adalah untuk mengetahui apakah model pembelajaran kooperatif tipe STAD dapat meningkatkan motivasi belajar IPA bagi siswa kelas VII G SMP 3 Jekulo kabupaten Kudus pada materi Gejala Alam dan dapat mengetahui peningkatan prestasi belajar IPA bagi siswa kelas VII G SMP 3 Jekulo kabupaten Kudus pada materi Gejala Alam. Penelitian ini dilaksanakan selama 7 bulan yang dimulai dari awal bulan November 2012 sampai bulan Mei 2013. Hasil penelitian ini menyebutkan melalui  pembelajaran kooperatif tipe STAD (Student Team Achievement Division) dapat meningkatkan motivasi belajar IPA materi Gejala Alam dari kondisi awal motivasi belajar IPA rendah ke kondisi akhir motivasi belajar IPA tinggi. Dari hasil penelitian juga menyebutkan melalui pembelajaran kooperatif tipe STAD (Student Team Achievement Division) dapat meningkatkan prestasi belajar IPA pada materi Gejala Alam dari kondisi awal prestasi belajar IPA rerata 47,5 ke kondisi akhir rerata 76,32. Dapat disimpulkan baik secara teoritik maupun empirik bahwa pembelajaran kooperatif tipe STAD (Student Team Achievement division) dapat meningkatkan prestasi  belajar IPA.